Efficient Alkaline Water/Seawater Hydrogen Evolution by a Nanorod‐Nanoparticle‐Structured Ni‐MoN Catalyst with Fast Water‐Dissociation Kinetics. Issue 21 (24th April 2022) - Wu, Libo; Zhang, Fanghao; Song, Shaowei; Ning, Minghui; Zhu, Qing; Zhou, Jianqing; Gao, Guanhui; Chen, Zhaoyang; Zhou, Qiancheng; Xing, Xinxin; Tong, Tian; Yao, Yan; et al.
Abstract: Achieving efficient and durable nonprecious hydrogen evolution reaction (HER) catalysts for scaling up alkaline water/seawater electrolysis is desirable but remains a significant challenge. Here, a heterogeneous Ni‐MoN catalyst consisting of Ni and MoN nanoparticles on amorphous MoN nanorods that can sustain large‐current‐density HER with outstanding performance is demonstrated. The hierarchical nanorod–nanoparticle structure, along with a large surface area and multidimensional boundaries/defects endows the catalyst with abundant active sites. The hydrophilic surface helps to achieve accelerated gas‐release capabilities and is effective in preventing catalyst degradation during water electrolysis. Theoretical calculations further prove that the combination of Ni and MoN effectively modulates the electron redistribution at their interface and promotes the sluggish water‐dissociation kinetics at the Mo sites. Consequently, this Ni‐MoN catalyst requires low overpotentials of 61 and 136 mV to drive current densities of 100 and 1000 mA cm −2, respectively, in 1 m KOH and remains stable during operation for 200 h at a constant current density of 100 or 500 mA cm −2 . This good HER catalyst also works well in alkaline seawater electrolyte and shows outstanding performance toward overall seawater electrolysis with ultralow cell voltages. Abstract : Nanorod–nanoparticle‐structured Ni‐MoN is prepared as an efficient HER catalyst for alkaline water and seawater electrolysis. Benefiting from the high and stable catalytic performance, this Ni‐MoN can be combined with stainless‐steel mat for overall water/seawater electrolysis. This assembled electrolyzer can be driven by a thermoelectric module to generate hydrogen.